PENGARUH KEPEMIMPINAN, KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - M, Nurwani (Universitas Muhammadiyah Parepare, 2020)
This research has the goal of knowing whether leadership, communication, and work discipline variables partially and simultaneously affect employee performance. The free variables in this study were leadership, communication, and work discipline while bound variables were employee performance. This research was conducted on the employees of PT. Bosowa Berlian Motor Branch Parepare which numbered 37 people. The type of research that quantitative research uses. Methods of collecting observational data, interviews, and questionnaires. For data analysis using validity test, realization test, multiple linear regression, partial test, simultaneous test, determination test (R square). The results showed that partially and simultaneously variable leadership, Communication, Work Discipline to Employee performance.